Laminate

JP2025042347APending Publication Date: 2025-03-27MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023149296
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

Smart Images

  • Figure 2025042347000001
    Figure 2025042347000001
  • Figure 2025042347000002
    Figure 2025042347000002
  • Figure 2025042347000003
    Figure 2025042347000003
Patent Text Reader

Abstract

To provide a laminate excellent in adhesiveness between a layer composed of an ethylenic copolymer composition and a layer containing a fiber material.SOLUTION: In the laminate, a layer [I] composed of an ethylenic copolymer composition and a layer [II] containing a fiber material are in contact with each other, the ethylenic copolymer composition containing: an ethylene / α-olefin / 5-vinyl-2-norbornene copolymer (P) which satisfies specific requirements; and an ethylene / α-olefin / nonconjugated polyene copolymer (Q) which is a copolymer other than the copolymer (P), satisfies specific requirements, and contains ethylene [A], a C4-20 α-olefin [B], and a nonconjugated polyene [C].SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to laminates and industrial belts. [Background technology]

[0002] Ethylene-α-olefin-non-conjugated polyene copolymers such as ethylene-propylene-diene copolymer (EPDM) generally have excellent weather resistance, heat resistance, and ozone resistance, and are used in industrial automotive parts, industrial rubber products, electrical insulation materials, civil engineering and construction materials, rubberized fabrics, etc.

[0003] Conventional ethylene-α-olefin-non-conjugated polyene copolymers have the disadvantage of inferior adhesion to synthetic fibers compared to polar rubbers such as nitrile rubber, chloroprene rubber, and chlorosulfonated polyethylene. As a method for solving this disadvantage, it has been disclosed that the adhesion between ethylene-α-olefin-non-conjugated polyene copolymers and synthetic fibers is improved by using an adhesive solution of a chlorosulfonated copolymer (Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 42-23632 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in today's world where environmental issues such as non-halogenation are a concern, it is difficult to say that such adhesion technology that utilizes the polarity of halogenation is optimal. Also, as a conventional adhesion method, a method is known in which synthetic fibers are treated with resorcinol-formaldehyde-latex (RFL treatment), then embedded in rubber and crosslinked to adhere. More specifically, a method is known in which isocyanates or isocyanuric acid derivatives are used in the RFL treatment. However, even if these methods are applied to the case where an ethylene-based copolymer composition containing an ethylene-α-olefin-non-conjugated polyene copolymer is used as the rubber, it is difficult to obtain sufficient adhesion.

[0006] An object of the present invention is to provide a laminate having excellent adhesion between a layer made of an ethylene-based copolymer composition and a layer containing a fiber material. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above-mentioned problems, and have found that the above-mentioned problems can be solved by a laminate in which a layer [I] made of an ethylene-based copolymer composition containing an ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) satisfying specific requirements and an ethylene-α-olefin-non-conjugated polyene copolymer (Q) satisfying specific requirements is in contact with a layer [II] containing a fibrous material, thereby completing the present invention.

[0008] That is, the present invention relates to, for example, the following [1] to [9]. [1] An ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) that satisfies the following requirements (i) to (vi); an ethylene-α-olefin-non-conjugated polyene copolymer (Q) which is a copolymer other than the copolymer (P) and which contains ethylene [A], an α-olefin [B] having 4 to 20 carbon atoms, and a non-conjugated polyene [C] and satisfies the following requirements (1) to (4); A layer [I] made of an ethylene-based copolymer composition comprising A laminate in contact with a layer [II] containing a fibrous material. (i) The weight average molecular weight is in the range of 100 to 50,000. (ii) The molecular weight distribution (Mw / Mn, Mw: weight average molecular weight, Mn: number average molecular weight) measured by gel permeation chromatography (GPC) is 2.7 or less. (iii) 13 The intensity ratio Tαβ / Tαα of the C-NMR spectrum is 0.0 to 0.1. (iv) The content of structural units derived from 5-vinyl-2-norbornene is within the range of 0.1 to 20.0 mass %. (v) The structural units derived from 5-vinyl-2-norbornene contain an endo structure and an exo structure, and the ratio of the endo structure / exo structure is 2.5 or less. (vi) The intrinsic viscosity [η] measured in decahydronaphthalene at 135° C. is in the range of 0.01 to 0.8 dl / g. (1) the molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 50 / 50 to 90 / 10; (2) the content of the structural unit derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from the above [A], [B] and [C]; (3) Mooney viscosity ML at 100°C (1+4) 100°C is 5 to 150; (4) The B value represented by the following formula (I) is 1.20 or more. B value=([EX]+2[Y]) / [2×[E]×([X]+[Y])]···(I) [Here, [E], [X] and [Y] respectively represent the mole fractions of ethylene [A], α-olefin [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.]

[0009] [2] The laminate according to [1], wherein the α-olefin [B] having 4 to 20 carbon atoms is 1-butene.

[0010] [3] The laminate according to [1] or [2], wherein the ethylene-based copolymer composition contains 0.1 to 30 parts by mass of the ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) per 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (Q).

[0011] [4] The laminate according to any one of [1] to [3], wherein the ethylene-based copolymer composition further contains an organic peroxide as a crosslinking agent.

[0012] [5] The laminate according to any one of [1] to [4], wherein the ethylene-based copolymer composition contains 0.1 to 20 parts by mass of stearic acid per 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (Q).

[0013] [6] The laminate according to any one of [1] to [5], wherein the layer [I] is a layer obtained by crosslinking the ethylene-based copolymer composition.

[0014] [7] The laminate according to any one of [1] to [6], wherein the fiber material of the layer [II] contains a fiber treated with resorcinol-formaldehyde-latex.

[0015] [8] The laminate according to any one of [1] to [7], wherein the fiber material of the layer [II] is canvas.

[0016] [9] An industrial belt having the laminate according to any one of [1] to [8]. Effect of the Invention

[0017] According to the present invention, it is possible to provide a laminate having excellent adhesion between a layer made of an ethylene-based copolymer composition and a layer containing a fiber material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] <Laminate> The laminate of the present invention is a laminate in which a layer [I] made of an ethylene copolymer composition is in contact with a layer [II] containing a fiber material. Each component of the laminate of the present invention will be described below.

[0019] <Layer [I] made of ethylene-based copolymer composition> [Ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P)] The ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) contained in the ethylene-based copolymer composition satisfies the following requirements (i) to (vi). Such a specific ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) may be abbreviated as "ethylene-based copolymer (P)".

[0020] [Requirement (i)] The weight average molecular weight is in the range of 100 to 50,000, preferably 1,000 to 35,000, and more preferably 1,500 to 30,000. When the weight average molecular weight of the ethylene-based copolymer (P) is within the above range, the ethylene-based copolymer (P) has good flowability during molding, can be molded at low pressure, and the mechanical strength of the obtained laminate is high.

[0021] [Requirement (ii)] The molecular weight distribution (Mw / Mn, Mw: weight average molecular weight, Mn: number average molecular weight) measured by gel permeation chromatography (GPC) is 2.7 or less, preferably 2.6 or less, and more preferably 2.5 or less. When the ethylene copolymer (P) has the above molecular weight distribution, the resulting laminate has high mechanical strength.

[0022] [Requirement (iii)] 13 The intensity ratio Tαβ / Tαα in the C-NMR spectrum is 0.0 to 0.1, preferably 0 to 0.05, and more preferably 0 to 0.01. Here, as shown below, Tαβ is 13 indicates the peak intensity of a carbon atom having branches at the α- and β-positions in a C-NMR spectrum, and Tαα indicates the peak intensity of a carbon atom having branches at both α-positions.

[0023] [ka]

[0024] When the strength ratio Tαβ / Tαα is within the above range, the mechanical strength of the obtained laminate is high.

[0025] [Requirement (iv)] The content of structural units derived from 5-vinyl-2-norbornene (hereinafter sometimes referred to as "VNB") is in the range of 0.1 to 20.0 mass %, preferably 0.5 to 15.0 mass %, and more preferably 1.0 to 10.0 mass %. When the content of the structural unit derived from VNB is within the above range, rapid curing can be achieved, shortening the molding cycle, and the mechanical strength of the resulting laminate is high.

[0026] [Requirement (v)] The constitutional units derived from VNB contain an endo structure and an exo structure, and the ratio of the endo structure / exo structure is 2.5 or less, preferably 2.4 or less, and more preferably 2.3 or less. When the ratio of endo structure / exo structure is within the above range, the mechanical strength of the resulting laminate is high. The endo body is 13 The C-NMR spectrum shows a peak intensity of a carbon atom (9n) at around 114 ppm, and the exo isomer 13 The peak intensity (9x) of the carbon atom at about 111.5 ppm in the C-NMR spectrum is shown.

[0027] [ka]

[0028] <Measurement of the intensity ratio Tαβ / Tαα and the endo / exo structure ratio> The intensity ratio Tαβ / Tαα and the endo structure / exo structure ratio can be determined as follows. Copolymer 13 The C-NMR spectrum is measured, for example, using a 400 MHz NMR measurement device manufactured by JEOL Ltd. The measurement is performed at 67.8 MHz, 25°C, and d6-benzene (128 ppm) as the standard, using a mixed solution of hexachlorobutadiene / d6-benzene = 2 / 1 (volume ratio) prepared so that the sample concentration is 5 wt%. 13 C-NMR spectra are analyzed according to the suggestions of Lindeman Adams (Analysis Chemistry 43, p. 1245 (1971)) and JC Randal (Review Macromolecular Chemistry Physics, C29, 201 (1989)).

[0029] [Requirement (vi)] The intrinsic viscosity [η] measured in decahydronaphthalene at 135° C. is in the range of 0.01 to 0.8 dl / g, preferably 0.03 to 0.6 dl / g, and more preferably 0.05 to 0.5 dl / g. When the intrinsic viscosity [η] is within the above range, the ethylene copolymer (P) has good fluidity during molding, can be molded at low pressure, and the mechanical strength of the obtained laminate is high.

[0030] The ethylene-based copolymer (P) has a molar ratio of structural units derived from ethylene (a1) to structural units derived from an α-olefin (a2) having 3 to 20 carbon atoms [(a1) / (a2)] of preferably 40 / 60 to 99.9 / 0.1, more preferably 50 / 50 to 90 / 10, further preferably 55 / 45 to 85 / 15, and particularly preferably 55 / 45 to 78 / 22. By using the ethylene copolymer (P) that satisfies the above requirements, a laminate excellent in rubber elasticity, mechanical strength and flexibility can be obtained. The ethylene content (content of structural units derived from ethylene (a1)) and the α-olefin content (content of structural units derived from α-olefin (a2)) in the ethylene copolymer (P) are 13 It can be determined by C-NMR.

[0031] Examples of the α-olefin (a2) having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, etc. Among these, α-olefins having 3 to 8 carbon atoms such as 1-butene, 1-hexene, and 1-octene are preferred, propylene and 1-butene are more preferred, and propylene is even more preferred. Such α-olefins are preferred because the raw material costs are relatively low, the ethylene-based copolymer (P) obtained from the α-olefin exhibits excellent mechanical properties, and further, the laminate obtained from the ethylene-based copolymer (P) has rubber elasticity. The above α-olefins (a2) may be used alone or in combination of two or more.

[0032] <Production method of ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P)> The ethylene copolymer (P) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst. For example, the metallocene catalyst and the production method using the catalyst can be adopted from the examples described in International Publication No. 2015 / 122415, particularly paragraphs

[0249] to

[0320] of the publication.

[0033] [Ethylene-α-olefin-non-conjugated polyene copolymer (Q)] The ethylene-α-olefin-non-conjugated polyene copolymer (Q) contained in the ethylene-based copolymer composition is a copolymer other than the ethylene-based copolymer (P), contains structural units derived from ethylene [A], structural units derived from an α-olefin [B] having 4 to 20 carbon atoms, and structural units derived from a non-conjugated polyene [C], and satisfies the following requirements (1) to (4). Such a specific ethylene-α-olefin-non-conjugated polyene copolymer (Q) may be abbreviated as "ethylene-based copolymer (Q)".

[0034] The α-olefin [B] having 4 to 20 carbon atoms and the non-conjugated polyene [C] may each be used alone or in combination of two or more.

[0035] [Requirement (1)] The molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 50 / 50 to 90 / 10. The ethylene copolymer (Q) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperature and tensile strength at room temperature. The lower limit of [A] / [B] is preferably 55 / 45, more preferably 60 / 40, and even more preferably 65 / 35. The upper limit of [A] / [B] is preferably 85 / 15, more preferably 80 / 20, and even more preferably 75 / 25.

[0036] [Requirement (2)] The content of the structural units derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol %, relative to 100 mol % of the total of the structural units derived from the ethylene [A], the structural units derived from the α-olefin [B] having 4 to 20 carbon atoms, and the structural units derived from the non-conjugated polyene [C]. The lower limit of the content of the structural unit derived from the non-conjugated polyene [C] is preferably 0.5 mol %. The upper limit of the content of the structural unit derived from the non-conjugated polyene [C] is preferably 4.0 mol %, more preferably 3.5 mol %, and further preferably 3.0 mol %. When the content of the structural unit derived from the non-conjugated polyene [C] is within the above range, the ethylene-based copolymer (Q) has sufficient crosslinkability and flexibility.

[0037] [Requirement (3)] Mooney viscosity at 100℃ ML (1+4) The temperature at 100°C is in the range of 5 to 150, preferably 10 to 60, and more preferably 20 to 40.

[0038] When the Mooney viscosity at 100°C is within the above range, the ethylene-based copolymer (Q) has excellent roll processability even in a high-hardness oil-less formulation, and also exhibits good post-treatment quality (ribbon handling property) and has excellent rubber physical properties.

[0039] The ethylene copolymer (Q) has a Mooney viscosity of ML at 125°C. (1+4) The temperature at 125°C is preferably in the range of 5 to 100, more preferably 10 to 95, and further preferably 10 to 60. When the Mooney viscosity at 125° C. is within the above range, the ethylene copolymer (Q) has good processability and flowability, and also exhibits good post-treatment quality (ribbon handling property) and has excellent rubber physical properties.

[0040] [Requirement (4)] The B value represented by the following formula (I) is 1.20 or more. B value=([EX]+2[Y]) / [2×[E]×([X]+[Y])]···(I) [Here, [E], [X] and [Y] respectively represent the mole fractions of ethylene [A], α-olefin [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.] The B value represented by the above formula (I) is preferably in the range of 1.20 to 1.80, and particularly preferably 1.22 to 1.40. When the B value is 1.20 or more, the compression set at low temperatures is small, and an ethylene copolymer (Q) having an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature can be obtained.

[0041] Examples of the α-olefin [B] having 4 to 20 carbon atoms include 1-butene having 4 carbon atoms, 1-nonene having 9 carbon atoms, 1-decene having 10 carbon atoms, 1-nonadecene having 19 carbon atoms, and 1-eicosene having 20 carbon atoms, which have a linear structure without a side chain, as well as 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, and 12-ethyl-1-tetradecene, which have a side chain. Among these, α-olefins having 4 to 10 carbon atoms are preferred, and 1-butene, 1-hexene, 1-octene, and the like are particularly preferred, with 1-butene being particularly suitable.

[0042] Examples of the non-conjugated polyene [C] include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, and 5-isopropylidene-2-norbornene. cyclic non-conjugated dienes such as bornene and 6-chloromethyl-5-isopropenyl-2-norbornene; and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,5-norbornadiene, 1,3,7-octatriene, 1,4,9-decatriene, 4,8-dimethyl-1,4,8-decatriene, and 4-ethylidene-8-methyl-1,7-nonadiene. Among these, linear non-conjugated dienes such as 1,4-hexadiene, and cyclic non-conjugated dienes such as 5-ethylidene-2-norbornene, 5-ethylidene-2-norbornene, and 5-vinyl-2-norbornene are preferred, cyclic non-conjugated dienes are more preferred, 5-ethylidene-2-norbornene and 5-vinyl-2-norbornene are even more preferred, and 5-ethylidene-2-norbornene is particularly preferred.

[0043] Examples of the ethylene copolymer (Q) include ethylene-1-butene-1,4-hexadiene copolymer, ethylene-1-pentene-1,4-hexadiene copolymer, ethylene-1-hexene-1,4-hexadiene copolymer, ethylene-1-heptene-1,4-hexadiene copolymer, ethylene-1-octene-1,4-hexadiene copolymer, ethylene-1-nonene-1,4-hexadiene copolymer, ethylene-1-decene-1,4-hexadiene copolymer, ethylene-1-butene-1,4-hexadiene copolymer, 1,4-Hexadiene copolymer, Ethylene-1-butene-5-ethylidene-2-norbornene copolymer, Ethylene-1-pentene-5-ethylidene-2-norbornene copolymer, Ethylene-1-hexene-5-ethylidene-2-norbornene copolymer, Ethylene-1-heptene-5-ethylidene-2-norbornene copolymer, Ethylene-1-octene-5-ethylidene-2-norbornene copolymer, Ethylene-1-nonene-5-ethylidene-2-norbornene copolymer, Ethylene-1-decene-5-ethylidene Ethylene-1-butene-1-octene-5-ethylidene-2-norbornene copolymer, Ethylene-1-butene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-pentene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-hexene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, Ethylene-1-heptene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer Examples of the ethylene copolymer (Q) include ethylene-1-octene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, ethylene-1-nonene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, ethylene-1-decene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer, and ethylene-1-butene-1-octene-5-ethylidene-2-norbornene-5-vinyl-2-norbornene copolymer. One or more types of ethylene copolymer (Q) are used as necessary.

[0044] <Production method of ethylene-α-olefin-non-conjugated polyene copolymer (Q)> The ethylene copolymer (Q) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst. As the metallocene catalyst and the production method using the catalyst, for example, the examples described in International Publication No. 2015 / 122415, particularly paragraphs

[0249] to

[0320] of the publication can be adopted.

[0045] <Ethylene-Based Copolymer Composition> The ethylene-based copolymer composition according to the present invention contains the ethylene-based copolymer (P) and the ethylene-based copolymer (Q), and therefore has excellent adhesive strength between the layer [I] made of the copolymer composition and the layer [II] containing a fiber material.

[0046] The ethylene-based copolymer composition forming the layer [I] of the laminate of the present invention preferably contains the ethylene-based copolymer (P) in an amount of 0.1 to 30 parts by mass, more preferably 3 to 20 parts by mass, and even more preferably 5 to 15 parts by mass, per 100 parts by mass of the ethylene-based copolymer (Q). When the content of the ethylene copolymer (P) is within the above range, the layer [I] in the laminate of the present invention has excellent adhesive strength with the layer [II] containing a fibrous material.

[0047] The ethylene copolymer composition has a Mooney viscosity ML at 100°C in the composition before the crosslinking agent is added. (1+4) is preferably 1 to 100, and more preferably 20 to 90. When the Mooney viscosity at 100° C. is within the above range, the ethylene copolymer composition has excellent processability, good post-treatment quality (ribbon handling property) and excellent rubber physical properties.

[0048] In addition to the ethylene-based copolymer (P) and the ethylene-based copolymer (Q), the ethylene-based copolymer composition may contain other components according to the desired purpose within the range that does not impair the effects of the present invention. The other components may contain at least one selected from, for example, surfactants, resorcinol compounds, melamine resins, crosslinking agents, crosslinking assistants, vulcanization accelerators, vulcanization accelerator assistants, fillers, softeners, antioxidants, processing assistants, activators, heat stabilizers, weather stabilizers, antistatic agents, colorants, lubricants, thickeners, etc. Each of the additives may be used alone or in combination of two or more kinds.

[0049] The ethylene-based copolymer composition can be obtained by kneading the ethylene-based copolymer (P), the ethylene-based copolymer (Q), and other components that are further blended as necessary, using a conventionally known kneading machine, such as an internal mixer (internal mixer) such as a Banbury mixer, a kneader, or an Intermix, or a roll.

[0050] Surfactants Examples of surfactants include nonionic surfactants, cationic surfactants, anionic surfactants and amphoteric surfactants.

[0051] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene derivatives, polyoxyethylene polyoxypropylene glycol, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate. sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, glycerol monostearate, glycerol monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan sesquioleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamines, and alkyl alkanolamides.

[0052] Examples of cationic surfactants include coconut amine acetate, stearyl amine acetate, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, alkyl benzyl dimethyl ammonium chloride, bishydroxyethyl alkyl (C8-18) methyl ammonium chloride, bis (polyoxyethylene) alkyl (C8-18) methyl ammonium chloride, and bishydroxyethyl oleyl methyl ammonium chloride. Examples of commercially available cationic surfactants include Lipocard (registered trademark) (e.g., Lipocard 2HT flakes), Liposocard (registered trademark) (both manufactured by Lion Specialty Chemicals Co., Ltd.).

[0053] Examples of anionic surfactants include mixed fatty acid soda soap, semi-hardened beef tallow fatty acid soda soap, sodium stearate soap, semi-hardened beef tallow fatty acid potassium soap, potassium oleate soap, castor oil potassium soap, sodium lauryl sulfate, sodium higher alcohol sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium alkyldiphenyletherdisulfonate, potassium alkylphosphate, sodium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, sodium alkane sulfonate, and the sodium salt of β-naphthalenesulfonic acid formalin condensate.

[0054] Examples of amphoteric surfactants include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl dimethylamine oxide. The surfactant is preferably at least one surfactant selected from the group consisting of cationic surfactants and anionic surfactants, and more preferably a cationic surfactant.

[0055] The content of the surfactant is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, based on 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (Q). When the content of the surfactant is within the above range, the layer [I] made of the ethylene copolymer composition has excellent adhesion to the layer [II] containing a fiber material.

[0056] Resorcinol compounds (M) The resorcinol compound (M) is not particularly limited as long as it acts mainly as an adhesive, and examples thereof include modified resorcinol-formaldehyde resin, resorcin, and resorcinol-formaldehyde (RF) resin. Among these, modified resorcinol-formaldehyde resin is preferably used in terms of transpiration, hygroscopicity, and compatibility with rubber.

[0057] The modified resorcinol-formaldehyde resin may be, for example, one represented by the following general formulas (M1) to (M3). Among these, the one represented by the following general formula (M1) is particularly preferred.

[0058] [ka]

[0059] [ka]

[0060] [ka]

[0061] These resorcinol compounds (M) are manufactured and sold by Taoka Chemical Industry Co., Ltd. under the trade name Sumikanol 620 (modified resorcinol-formaldehyde resin). The content of the resorcinol compound (M) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (Q). By setting the content of the resorcinol compound (M) within the above range, it is possible to sufficiently improve roll processability while suppressing an increase in cost.

[0062] Melamine resin (N) The melamine resin (N) is not particularly limited as long as it acts mainly as an adhesive aid, and examples thereof include methylated formaldehyde-melamine polymers and hexamethylenetetramine. Among these, methylated formaldehyde-melamine polymers are preferably used in terms of transpiration, hygroscopicity, and compatibility with rubber.

[0063] As the methylated product of the formaldehyde-melamine polymer, for example, the one represented by the following general formula (N1) is preferably used.

[0064] [ka]

[0065] Among the melamine resins (N), a mixture of compounds represented by the above general formula (N1) is preferred, and a mixture containing 43 to 44% by weight of a compound where n=1, 27 to 30% by weight of a compound where n=2, and 26 to 30% by weight of a compound where n=3 is particularly preferred. Melamine resin (N) is manufactured and sold by Taoka Chemical Industry Co., Ltd. under the trade name Sumikanol 507AP (methylated formaldehyde-melamine polymer). The content of the melamine resin (N) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the ethylene-α-olefin-non-conjugated polyene copolymer (Q).

[0066] <Crosslinking Agent> Examples of the crosslinking agent include crosslinking agents generally used for crosslinking rubber, such as organic peroxides, phenolic resins, sulfur-based compounds, hydrosilicone-based compounds, amino resins, quinone or its derivatives, amine-based compounds, azo-based compounds, epoxy-based compounds, isocyanate-based compounds, and quinone dioxime-based crosslinking agents such as p-quinone dioxime. Among these, organic peroxides and sulfur-based compounds are preferred.

[0067] Examples of organic peroxides include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl peroxybenzoate, ert-butylperoxyisopropyl carbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.

[0068] When an organic peroxide is used as a crosslinking agent, the amount of the organic peroxide in the ethylene-based copolymer composition is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, and even more preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (Q). When the amount of the organic peroxide is within the above range, no bloom occurs on the surface of the obtained molded article, and the ethylene copolymer composition exhibits excellent crosslinking properties.

[0069] When an organic peroxide is used as the crosslinking agent, it is preferable to use a crosslinking assistant in combination. The crosslinking auxiliary is a compound that acts as a crosslinking reaction catalyst when blended together with the crosslinking agent when the ethylene copolymer composition is crosslinked by heating. Examples of the crosslinking aid include acrylic crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate; allyl crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide crosslinking aids; and divinylbenzene.

[0070] When a crosslinking aid is used, the amount of the crosslinking aid in the ethylene copolymer composition is preferably 0.5 to 10 mol, more preferably 0.5 to 7 mol, and further preferably 1 to 6 mol, per mol of the organic peroxide.

[0071] When a sulfur-based compound is used as a crosslinking agent, examples of the compound include sulfur, sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, tetramethylthiuram disulfide, and selenium dithiocarbamate. Although sulfur is not a compound, it is classified as a sulfur-based compound in this specification for convenience.

[0072] When a sulfur-based compound is used as a crosslinking agent, the amount of the sulfur-based compound in the ethylene-based copolymer composition is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 7.0 parts by mass, and even more preferably 0.3 to 5.0 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (Q). When the amount of the sulfur-based compound is within the above range, no bloom occurs on the surface of the obtained molded article, and the ethylene-based copolymer composition exhibits excellent crosslinking properties.

[0073] When a sulfur-based compound is used as a crosslinking agent, it is preferable to use a vulcanization accelerator in combination. Examples of the vulcanization accelerator include N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, N,N'-diisopropyl-2-benzothiazole sulfenamide, 2-mercaptobenzothiazole (e.g., Suncerer M (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), 2-(4-morpholinodithio)benzothiazole (e.g., Noccelaer MDB-P (trade name; manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)), 2-(2,4-dinitrophenyl)mercaptobenzothiazole, 2-(2,6-dinitrophenyl)mercaptobenzothiazole, and the like. Thiazole-based vulcanization accelerators such as ethyl-4-morpholinothio)benzothiazole and dibenzothiazyl disulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); guanidine-based vulcanization accelerators such as diphenyl guanidine, triphenyl guanidine, and diorthotolyl guanidine; aldehyde amine-based vulcanization accelerators such as acetaldehyde-aniline condensation product and butyraldehyde-aniline condensation product; imidazoline-based vulcanization accelerators such as 2-mercaptoimidazoline; tetramethylthiuram monosulfide (for example, Sancerer DM (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (e.g., Sancerer TS (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetramethylthiuram disulfide (e.g., Sancerer TT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetraethylthiuram disulfide (e.g., Sancerer TET (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), tetrabutylthiuram disulfide (e.g., Sancerer TBT (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), and dipentamethylenethiuram tetrasulfide (e.g., Sancerer TRA (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)); zinc dimethyldithiocarbamate, diethyldithio Examples of such vulcanization accelerators include dithioacid salt vulcanization accelerators such as zinc carbamate, zinc dibutyldithiocarbamate (e.g., Sancerar PZ, Sancerar BZ, and Sancerar EZ (trade names; manufactured by Sanshin Chemical Industry Co., Ltd.)) and tellurium diethyldithiocarbamate; thiourea vulcanization accelerators such as ethylenethiourea (e.g., Sancerar BUR (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.), Sancerar 22-C (trade name; manufactured by Sanshin Chemical Industry Co., Ltd.)), N,N'-diethylthiourea, and N,N'-dibutylthiourea; and xanthate vulcanization accelerators such as zinc dibutylxatogenate.

[0074] When a vulcanization accelerator is used, the amount of the vulcanization accelerator in the ethylene-based copolymer composition is preferably 0.1 to 20 parts by mass, more preferably 0.2 to 15 parts by mass, and further preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (Q). When the blending amount of the vulcanization accelerator is within the above range, no bloom occurs on the surface of the obtained molded article, and the ethylene copolymer composition exhibits excellent crosslinking properties.

[0075] When a sulfur-based compound is used as the crosslinking agent, the ethylene-based copolymer preferably contains a vulcanization accelerator.

[0076] Examples of the vulcanization accelerator include zinc oxide (e.g., ZnO#1 and zinc oxide type 2, manufactured by Hakusui Tech Co., Ltd.), magnesium oxide, and activated zinc oxide (e.g., zinc oxide such as "META-Z102" (trade name, manufactured by Inoue Seki Kogyo Co., Ltd.)). When a vulcanization acceleration aid is used, the blending amount of the vulcanization acceleration aid in the ethylene copolymer composition is, for example, 1 to 20 parts by mass with respect to 100 parts by mass of the ethylene copolymer (Q).

[0077] Filler The filler is a known rubber reinforcing agent that is compounded in the rubber composition, and is usually an inorganic substance called carbon black or an inorganic reinforcing agent.

[0078] Specific examples of the filler include Asahi #55G, Asahi #60UG, and Asahi #70 (all manufactured by Asahi Carbon Co., Ltd.), Seast (V, SO, 116, 3, 6, 9, SP, TA, etc.) carbon black (manufactured by Tokai Carbon Co., Ltd.), and these carbon blacks that have been surface-treated with a silane coupling agent or the like, as well as silica, activated calcium carbonate, finely divided talc, finely divided silicic acid, light calcium carbonate, heavy calcium carbonate, talc, and clay.

[0079] These fillers may be used alone or in combination of two or more. As the filler, carbon black, light calcium carbonate, heavy calcium carbonate, talc, clay, etc. are preferably used.

[0080] When the ethylene-based copolymer composition contains a filler, the filler may be blended in an amount of preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, further preferably 30 to 100 parts by mass, and particularly preferably 40 to 60 parts by mass, relative to 100 parts by mass of the ethylene-based copolymer (Q).

[0081] <Softener> Examples of softeners include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and others, such as microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred.

[0082] When a softener is used, the blending amount of the softener in the ethylene-based copolymer composition is preferably 2 to 100 parts by mass, more preferably 10 to 100 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (Q).

[0083] <Anti-aging agent (stabilizer)> The life of a (crosslinked) molded article formed from an ethylene-based copolymer composition can be extended by blending an antioxidant (stabilizer) with the composition. Examples of the antioxidant include amine-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants.

[0084] Examples of the amine-based antiaging agents include aromatic secondary amine-based antiaging agents such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine. Examples of phenol-based antioxidants include dibutylhydroxytoluene and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Examples of sulfur-based anti-aging agents include thioether-based anti-aging agents such as bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butylphenyl]sulfide; dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate; 2-mercaptobenzoylimidazole, 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilaurylthiodipropionate, and distearylthiodipropionate.

[0085] When an antioxidant is used, the amount of the antioxidant in the ethylene-based copolymer composition is preferably 0.3 to 10 parts by mass, more preferably 1.0 to 9.0 parts by mass, further preferably 3.0 to 8.0 parts by mass, and particularly preferably 5.0 to 7.0 parts by mass, based on 100 parts by mass of the ethylene-based copolymer (Q). When the blending amount of the antioxidant is within the above range, no bloom occurs on the surface of the obtained molded article, and furthermore, the occurrence of vulcanization inhibition can be suppressed.

[0086] <Processing aids> As the processing aid, a wide variety of processing aids that are generally compounded with rubber can be used.Specific examples include ricinoleic acid, stearic acid, palmitic acid, lauric acid, barium stearate, zinc stearate, calcium stearate, zinc laurate, and esters.Of these, stearic acid is preferred.

[0087] The content of the processing aid is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, further preferably 0.4 to 5 parts by mass, and particularly preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the ethylene copolymer (Q). When the blending amount of the processing aid is within the above range, excellent processability such as kneading processability, extrusion processability, and injection moldability is obtained, which is preferable.

[0088] <Activator> Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.

[0089] When an activator is used, the amount of the activator in the ethylene copolymer composition is preferably 0.2 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, based on 100 parts by mass of the ethylene copolymer (Q).

[0090] <Layer containing fibrous material [II]> The layer [II] containing a fiber material that constitutes the laminate of the present invention contains a fiber material in at least a part of the layer.

[0091] <Textile materials> Examples of fiber materials for forming layer [II] include various known fiber materials, for example, natural fibers such as cotton and wood cellulose fibers; organic fiber materials such as fibers made of synthetic resins such as polyamide, polyester, polyvinyl alcohol, rayon, polyparaphenylene benzobisoxazole, polyethylene, polypropylene, polyarylate, polyimide, polyphenylene sulfide, polyether ether ketone, polylactic acid, polycaprolactone, polybutylene succinate, and fluorine-based polymers; and inorganic fiber materials such as glass fibers, PAN-based carbon fibers, pitch-based carbon fibers, alumina fibers, silicon carbide fibers, aluminum borate fibers, and potassium titanate whiskers.

[0092] These fiber materials may be long fibers (filaments) or short fibers (staples), and may be cord yarns, spun yarns, woven fabrics, knitted fabrics, canvas, nonwoven fabrics, and the like.

[0093] Examples of the polyamide include aliphatic polyamides such as nylon 6, nylon 6,6, and nylon 6,10; semi-aromatic polyamides such as polymetaxylylene adipamide (MXD6), polyhexamethylene terephthalamide (6T), and copolymer polyamides containing these units; and fully aromatic polyamides such as polybenzamide, poly-p-phenylene terephthalamide, and poly-m-phenylene isophthalamide.

[0094] In addition, these fiber materials may be surface-treated by a known method such as RFL treatment in order to improve adhesion between the fiber materials themselves or between the fiber materials and the layer [I] made of the ethylene-based copolymer composition.

[0095] <RFL Processing> RFL treatment is a process in which textile materials are treated with a treatment liquid (RFL liquid) containing resorcinol, formalin, and latex, and this RFL liquid is a mixture of the initial condensation product of resorcinol and formalin and rubber latex. Examples of rubber latex that can be used include styrene-butadiene-vinylpyridine terpolymer (VP), styrene-butadiene copolymer (SBR), chloroprene (CR), acrylonitrile-butadiene copolymer (NBR), hydrogenated NBR (H-NBR), chlorosulfonated ethylene (CSM), and natural rubber. These can be used alone or in a blend of two or more types.

[0096] <Method of manufacturing laminate> The laminate of the present invention comprises a layer [I] made of the above-mentioned ethylene copolymer composition and a layer [II] containing a fibrous material. To produce the laminate of the present invention, various known methods for producing laminates can be adopted. For example, a method of laminating a layer [I] made of an uncrosslinked ethylene copolymer composition previously molded by a known method with a layer [II] containing a fiber material, and then crosslinking the layer [I], a method of laminating a layer [I] previously crosslinked with a layer [II], or a method of extrusion coating the layer [I] on the layer [II], and then crosslinking the layer [I] can be mentioned.

[0097] Examples of methods for molding the uncrosslinked ethylene copolymer composition include methods of molding into a desired shape using a molding machine such as an extruder, a calendar roll, a press, an injection molding machine, or a transfer molding machine.

[0098] Simultaneously with or after the above-mentioned molding, the ethylene-based copolymer composition may be crosslinked to form a layer [I] made of the ethylene-based copolymer composition, and the layer [I] may be laminated (bonded) with a layer [II] containing a fiber material. Alternatively, an uncrosslinked ethylene-based copolymer composition may be molded into a desired shape by the above-mentioned method, and then laminated (bonded) with a layer [II] containing a fiber material, and then the layer [I] may be crosslinked.

[0099] The layer [I] made of the ethylene copolymer composition may be crosslinked by heating using a crosslinking agent or by irradiating with light, gamma rays or electron beams. In addition, when crosslinking, a mold may be used, or crosslinking may be performed without using a mold. When a mold is not used, the molding and crosslinking steps are usually performed continuously. As a heating method in the crosslinking tank, methods such as hot air, glass bead fluidized bed, UHF (ultra-high frequency electromagnetic wave), and steam can be used.

[0100] <<Applications of the laminate>> The laminate of the present invention is suitably used for automobile hoses, water hoses, gas hoses, industrial belts such as transmission belts and conveyor belts, and escalator handrails.

[0101] Examples of the automotive hose include brake hoses, radiator hoses, heater hoses, and air cleaner hoses. Examples of the power transmission belt include a V-belt, a flat belt, and a toothed belt. Examples of the conveyor belt include a light conveyor belt, a cylindrical belt, a rough top belt, a conveyor belt with a flange, a conveyor belt with a U-shaped guide, and a conveyor belt with a V-shaped guide. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" refers to "parts by mass".

[0103] The physical properties of each copolymer used in the following Preparation Examples were measured in the following manner. <Molar amount of each structural unit> The molar amount of each structural unit is: 1 The intensity was measured using a H-NMR spectrometer. Details of the measurement conditions are described in WO 2015 / 122415.

[0104] <Mooney viscosity> Mooney viscosity (ML (1+4) at 100 °C and 125 °C) was measured in accordance with JIS K6300 (1994) using a Mooney viscometer (Model SMV202 manufactured by Shimadzu Corporation).

[0105] Using o-dichlorobenzene-d4 / benzene-d6 (4 / 1 [v / v]) as the measurement solvent, at a measurement temperature of 120 °C, 13 a C-NMR spectrum (100 MHz, ECX400P manufactured by JEOL Ltd.) was measured and calculated based on the following formula (I). B value = ([EX] + 2[Y]) / {2 × [E] × ([X] + [Y])} ··· (I) Here, [E], [X], and [Y] represent the mole fractions of the structural units derived from ethylene [A], α-olefins [B] having 4 to 20 carbon atoms, and non-conjugated polyene [C], respectively, and [EX] represents the dyad chain fraction of ethylene [A] - α-olefins [B] having 4 to 20 carbon atoms.

[0106] In the following adjustment examples, the following copolymers were used. 1. Ethylene·α-olefin·non-conjugated polyene copolymer (Q) [Production Example 1] An ethylene·1-butene·5-ethylidene-2-norbornene (ENB) copolymer (Q-1) was obtained according to the description of [Synthesis Example C1] in International Publication No. 2015 / 122415.

[0107] The composition and physical properties of the copolymer (Q-1) obtained in Production Example 1 above are as follows. Structural unit derived from ethylene: 69.1 mol% Structural unit derived from 1-butene: 27.8 mol% Structural unit derived from ENB: 2.2 mol% Mooney viscosity ML (1+4) at 100 °C: 30 Mooney viscosity ML (1+4) at 125 °C: 22 B value: 1.3

[0108] 2. Ethylene-α-olefin-5-vinyl-2-norbornene copolymer (P) [Production Example 2] <Production of Copolymer (P-1)> Terpolymerization of ethylene, propylene, and 5-vinyl-2-norbornene was carried out continuously using a stainless steel polymerization vessel with an actual internal volume of 100 L (agitation speed: 250 rpm) equipped with an agitator blade. 45.5 L of hexane, 1.4 kg of ethylene, 6.8 kg of propylene, and 70 g of 5-vinyl-2-norbornene were fed into the liquid phase from the side of the polymerization vessel at a rate of 45.5 L per hour. 500 NL of hydrogen, 16 mmol of catalyst VO(OEt)Cl2, and 16 mmol of Al(Et) were also fed. 1.5 Cl 1.5 was fed continuously at a rate of 112 mmol. When the copolymerization reaction was carried out under the above conditions, a random copolymer, ethylene-propylene-5-vinyl-2-norbornene copolymer (P-1), was obtained in a homogeneous solution state. Thereafter, a small amount of methanol was added to the polymerization solution continuously withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the copolymer was separated from the solvent by steam stripping treatment and then vacuum dried at 55°C for 48 hours. The physical properties of the obtained ethylene-propylene-5-vinyl-2-norbornene copolymer (P-1) are shown in Table 1.

[0109] 3. Ethylene-α-olefin-non-conjugated polyene copolymer (q) The following ethylene-propylene-5-ethylidene-2-norbornene (ENB) copolymer (copolymer (q-1)) was used as the ethylene-α-olefin-non-conjugated polyene copolymer (q). The physical properties of copolymer (q-1) are shown in Table 1. Copolymer (q-1): Trade name Trilen 67 (manufactured by Uniroyal Co., Ltd.)

[0110] [Table 1]

[0111] [Adjustment example 1] Using a MIXTRON BBMIXER (Kobe Steel, BB-2 type, volume 1.7L, rotor 2WH), 100 parts of copolymer (Q-1) and 10 parts of copolymer (P-1) were mixed with 5 parts of ZnO#1 (Hakusui Tech Co., Ltd.) as a crosslinking aid, 1 part of stearic acid as a processing aid, 2 parts of Irganox 1010 (pentaerythritol tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate], BASF Co., Ltd.) as an antiaging agent, 4 parts of Sandant MB (2-mercaptobenzimidazole, Sanshin Chemical Industry Co., Ltd.) as an antiaging agent, and 50 parts of Asahi #70 (Asahi Carbon Co., Ltd.) as carbon black, and then kneaded to obtain compound 1. The mixing conditions for compound 1 were: rotor speed 40 rpm, floating weight pressure 3 kg / cm 2 The kneading time was 5 minutes, and the kneading discharge temperature was 144°C.

[0112] Next, after confirming that the temperature of Compound 1 had reached 40°C, 6.8 parts of dicumyl peroxide (DCP) (40% masterbatch) (product name: DCP-40C, manufactured by Kayaku Akzo Co., Ltd.) was added as a crosslinking agent to Compound 1 and kneaded using a 6-inch roll to obtain Compound 2. The kneading conditions for preparing compound 2 were as follows: roll temperature: front roll / rear roll = 50°C / 50°C, roll peripheral speed: front roll / rear roll = 18 rpm / 15 rpm, roll gap: 3 mm, and kneading time: 8 minutes to obtain compound 2.

[0113] <Evaluation of physical properties of uncrosslinked rubber> [Mooney Viscosity] Mooney Viscosity ML of Compound 2 (1+4) The viscosity was measured at 100°C using a Mooney viscometer (SMV-301 model, manufactured by Shimadzu Corporation) in accordance with JIS K6300 (1994). [Crosslinking (vulcanization) characteristic evaluation] The vulcanization rate (tC90) of Compound 2 at 170°C was measured using a vulcanization measuring device: MDR2000 (manufactured by ALPHATECHNOLOGIES) under the measurement conditions of a temperature of 170°C and a time of 30 minutes as follows. The torque change obtained under the conditions of constant temperature and constant shear rate was measured. The difference between the maximum torque (S'Max) and the minimum torque (S'Min): S'max-S'min [dNm], the time when the torque of the measured sample increased by 1 [dNm] after reaching the minimum torque S'min: TS1 [min], the time when the torque of the measured sample reached 90% of the minimum torque S'min and the maximum torque S'max was 100%: tc90, and MCR [dNm / min] were calculated. The smaller the tc90, the faster the vulcanization speed (crosslinking speed).

[0114] Evaluation of physical properties of vulcanized (crosslinked) products Compound 2 was pressed using a press molding machine at 170° C. for 15 minutes to produce a sheet (vulcanized product (crosslinked product)) having a thickness of 2 mm.

[0115] [Hardness test (Durometer-A)] The flat portions of the sheets were stacked to form a sheet having a thickness of 12 mm, and the hardness (JIS-A) was measured in accordance with JIS K6253.

[0116] [Tensile test: modulus, tensile stress at break, tensile elongation at break] The sheet was punched out to prepare a No. 3 dumbbell test piece described in JIS K6251 (1993). Using this test piece, a tensile test was performed according to the method specified in JIS K6251, section 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the tensile stress at an elongation rate of 25% (25% modulus (M25)), the tensile stress at an elongation rate of 50% (50% modulus (M50)), the tensile stress at an elongation rate of 100% (100% modulus (M100)), the tensile stress at an elongation rate of 200% (200% modulus (M200)), the tensile stress at an elongation rate of 300% (300% modulus (M300)), the tensile stress at break (TB), and the tensile elongation at break (EB) were measured.

[0117] [Tear strength] The tear strength was measured according to "Test method B-Procedure (a): Method using an unnotched angle-shaped test piece" specified in JIS-K6252-1. Specifically, an angle-shaped test piece with a thickness of 2 mm was prepared under the same conditions as for the preparation of the sheet, and this test piece was pulled at a speed of 500 mm / s to measure the maximum stress value (tear strength) (measurement temperature 25°C).

[0118] [Heat aging test] The sheet was subjected to a heat aging test in accordance with JIS K6257, in which the sheet was held at 180° C. for 70 hours. The hardness, tensile stress at break, and tensile elongation at break of the sheet after the heat aging test were measured in the same manner as in the above items [Hardness (Durometer-A)] and [Modulus, tensile stress at break, and tensile elongation at break].

[0119] AH (shore-A) was calculated from the difference in hardness before and after the heat aging test, and the rate of change after the test from the values ​​before the heat aging test to the values ​​before the test was calculated as Ac(TB) and Ac(EB), respectively, from the tensile stress at break (TB) and tensile elongation at break (EB) before and after the heat aging test.

[0120] [Adjustment example 2] A compound and a sheet were obtained in the same manner as in Preparation Example 1, except that commercially available Trilen 67 (manufactured by Uniroyal Co., Ltd.) was used instead of the ethylene-propylene-VNB copolymer (P-1) used in Preparation Example 1. The results are shown in Table 2.

[0121] [Table 2]

[0122] [Example 1] Compound 2 obtained according to the method described in Preparation Example 1 was placed on a woven fabric of RFL-treated nylon fiber (manufactured by Ayaha Kogyo Co., Ltd.), and pressed at 170°C for 15 minutes using a press molding machine to crosslink Compound 2. By the above method, a laminate was obtained in which a layer [I] made of a crosslinked ethylene copolymer composition and a layer [II] containing a fiber material were in contact with each other. [Peel strength] A test piece with a width of 25 mm was punched out from the obtained laminate, and a T-peel test was performed at a tensile speed of 50 mm / min to determine the peel strength (adhesive strength) between layer [I] and layer [II]. The results are shown in Table 3. The peeling state was also visually confirmed, and it was confirmed that layer [I] and layer [II] had been cohesively peeled off.

[0123] [Comparative Example 1] A laminate was obtained in the same manner as in Example 1, except that the compound obtained according to the method described in Preparation Example 2 was used, and then the peel strength was determined by the method described in Example 1. The results are shown in Table 3.

[0124] [Table 3]

Claims

1. An ethylene / α-olefin / 5-vinyl-2-norbornene copolymer (P) that satisfies the following requirements (i) to (vi): An ethylene / α-olefin / non-conjugated polyene copolymer (Q) which is a copolymer other than the copolymer (P) and which contains ethylene [A], an α-olefin [B] having 4 to 20 carbon atoms, and a non-conjugated polyene [C], and which satisfies the following requirements (1) to (4): A layer [I] made of an ethylene-based copolymer composition comprising A laminate in contact with a layer [II] containing a fibrous material. (i) The weight average molecular weight is in the range of 100 to 50,000. (ii) The molecular weight distribution (Mw / Mn, Mw: weight average molecular weight, Mn: number average molecular weight) measured by gel permeation chromatography (GPC) is 2.7 or less. (iii) 13 The intensity ratio Tαβ / Tαα in the C-NMR spectrum is 0.0 to 0.

1. (iv) The content of structural units derived from 5-vinyl-2-norbornene is in the range of 0.1 to 20.0 mass %. (v) The structural units derived from 5-vinyl-2-norbornene contain an endo structure and an exo structure, and the ratio of the endo structure / exo structure is 2.5 or less. (vi) The intrinsic viscosity [η] measured in decahydronaphthalene at 135° C. is in the range of 0.01 to 0.8 dl / g. (1) the molar ratio [[A] / [B]] of the structural unit derived from ethylene [A] to the structural unit derived from an α-olefin [B] having 4 to 20 carbon atoms is 50 / 50 to 90 / 10; (2) the content of the structural unit derived from the non-conjugated polyene [C] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from the above [A], [B] and [C]; (3) Mooney viscosity ML at 100°C (1+4) 100°C is 5 to 150; (4) The B value represented by the following formula (I) is 1.20 or more. B value = ([EX]+2[Y]) / [2×[E]×([X]+[Y])]...(I) [Here, [E], [X] and [Y] respectively represent the molar fractions of ethylene [A], the α-olefin [B] having 4 to 20 carbon atoms, and the non-conjugated polyene [C], and [EX] represents the dyad chain fraction of ethylene [A]-α-olefin [B] having 4 to 20 carbon atoms.]

2. 2. The laminate according to claim 1, wherein the α-olefin [B] having 4 to 20 carbon atoms is 1-butene.

3. The laminate according to claim 1, wherein the ethylene-based copolymer composition contains 0.1 to 30 parts by mass of the ethylene / α-olefin / 5-vinyl-2-norbornene copolymer (P) relative to 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (Q).

4. The laminate according to claim 1 , wherein the ethylene-based copolymer composition further comprises an organic peroxide as a crosslinking agent.

5. The laminate according to claim 1, wherein the ethylene-based copolymer composition contains 0.1 to 20 parts by mass of stearic acid per 100 parts by mass of the ethylene / α-olefin / non-conjugated polyene copolymer (Q).

6. The laminate according to claim 1 , wherein the layer [I] is a layer formed by crosslinking the ethylene-based copolymer composition.

7. The laminate of claim 1, wherein the fibrous material of the layer [II] comprises resorcinol-formaldehyde latex-treated fibers.

8. The laminate according to claim 1, wherein the textile material of the layer [II] is canvas.

9. An industrial belt comprising the laminate according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • JP1967-023632B